Representasi Dakwah Dalam Film Ayat-Ayat Cinta 2 (Analisis Semiotik Tokoh Fahri) - Laily Bunga Rahayu (IAIN Padangsidimpuan, 2022)
This research was conducted to examine the representation of da'wah contained in the film Ayat-Ayat Cinta 2. To find out, there is a focus on the problem, namely: How is the representation of da'wah in the film Ayat-Ayat Cinta 2?. To answer the focus of the problem above, the researcher uses a qualitative descriptive research approach with the type of media text research. The analytical method used is the semiotic analysis of the Roland Barthes model with two stages of significance, namely denotation and connotation as the key to the analysis. The data collection technique used is documentation. The results of this study, the representation of da'wah in the film Ayat-Ayat Cinta 2, including: trustworthiness, religious tolerance, patience and steadfastness and morals towards neighbors.Keywords: Representation of Da'wah, Film, Semiotics Roland Barthes.